The Seventh Semester Students’ Perception of Teaching and Learning English for Young Learners by Using Audio-Visual Style - Juwita Crestiani Maritu; Opik Dwi Indah; Hermini Hermini (Ethical Lingua: Journal of Language Teaching and Literature, 2021)
This research deals with The Seventh Year Students’ Perception of Teaching and Learning English for Young Learners by Using Audio-Visual Style at Palopo Cokroaminoto University. The population of this research was all English student of English Education Study Program in Palopo Cokroaminoto University in academic year 2020. The total number of population was 10 students. The researcher used the random sampling. The instrument in this research is questionnaire comprise five questions and analyzed by qualitative. Based on the findings and discussion in the previous chapter, the researcher concludes that the seventh year students’ perception of teaching and learning English for young learners by using audio-visual style at Palopo Cokroaminoto University is positive. It is supported by students’ answer that audio-visual style is appropriate in learning English for young learner because the students can remember information presented in picture by looking if student does not has strong skill to be listened because in audio-visual not only can be seen but also can be listened so the student can understand material easier. Besides that audio-visual has sound and interesting picture so does not make student get bored and has spirit in learning.